Effectiveness test of Diploknema oligomera extracts to the decrease in glucose levels in alloxan-induced BALB/c male mice - SITI FAIZAH; KARTINI ERIANI; ROSNIZAR ROSNIZAR (Nusantara Bioscience, 2023)
Abstract. Faizah S, Eriani K, Rosnizar. 2023. Effectiveness test of Diploknema oligomera extracts to the decrease in glucose levels in alloxan-induced BALB/c male mice. Nusantara Bioscience 15: 143-148. People with diabetes mellitus usually consume chemical drugs to lower their blood glucose levels which cause side effects and require a reasonably high cost. Therefore, alternative natural medicines (phytopharmaceuticals) that are safer and more affordable are needed. Punti fruit (Diploknema oligomera H.J Lam) has the potential as an antihyperglycemic agent that can lower glucose levels in the blood because the punti fruit contains flavonoid compounds, tannins, terpenoids, and saponins. These secondary metabolites can reduce blood glucose levels. This research used an experimental method with a completely randomized design, six treatments, and four replications. This study used 24 BALB/C (Mus musculus Linnaeus, 1758) male mice grouped into six treatments, namely normal control treatment (P1), negative control by giving alloxan 150 mg/kg bw (P2), positive control by giving glibenclamide dose of 0.65 mg/kg body weight (bw) (P3), ethanol extract of punti fruit dose of 250 mg/kg bw (P4), ethanol extract of punti fruit dose of 500 mg/kg body weight (P5) and ethanol extract of punti fruit dose of 1,000 mg/kg bw (P6). The results proved that administering punti extract (P3, P4, P5) for 14 could reduce blood glucose levels in male diabetic mice with a percentage reduction of 33.6%, 37.4%, and 52.7%, and treatment-positive control decreased blood glucose by 32.6%. The conclusion showed that the ethanol extract of punti fruit at a dose of 1,000 mg/kg bw could effectively reduce blood glucose levels in diabetic mice compared to a dose of 250 mg/kg bw, 500 mg/kg bw and 0.65 mg/kg glibenclamide kg bw. Therefore, punti fruit can be used as a drug candidate to be developed as phytopharmaceuticals in treating diabetes mellitus.